Recovery of the intrinsic thermoelectric properties of CaMn0.98Nb0.02O3 in 2-terminal geometry using Ag infiltration. (July 2017) - Boldrin, D.; Boldrin, P.; Ruiz-Trejo, E.; Cohen, L.F.
Abstract: Oxide based thermoelectric (TE) materials offer several advantages over currently used intermetallic alloys due to their chemical and thermal stability at high temperatures, non-toxic elements, low cost and ease of manufacture. However, incorporation of oxides into thermoelectric generators (TEGs) is hindered by factors such as the requirement for polycrystalline materials over single crystals and the large electrode/ceramic contact resistances. The latter significantly limits the performance efficiency of a working TEG. Here we report the TE properties of Ag infiltrated polycrystalline CaMn0.98 Nb0.02 O3 ceramics. We demonstrate that by using this route the intrinsic TE properties of this material are fully recovered in 2-terminal geometry through Ag infiltration, thereby overcoming the electrode TEG contact problem. This synthetic route provides opportunities for bridging the performance gap between the intrinsic TE and TEG device properties of oxides. Graphical abstract: Image 1